Narrativas Visuais: Uma investigação da evolução do fotojornalismo em O Progresso (OP) de Imperatriz (MA) de 1970 a 2023 - SILVA, Edmara Silva da (2024)
This research aims to investigate the development of photojournalism in Imperatriz (MA), using the printed newspaper O Progresso (OP), the oldest newspaper in the city, as the study object. The study spans the years from 1970 to 2023. To achieve this purpose, theoretical and methodological concepts related to Western photojournalism were applied, as discussed by Sousa (2004). Additionally, photographic and semiotic analysis of images was conducted, drawing from the perspectives of Mauad (1990, 1996, 2005) and Joly (2012, 2017, 2019). The research aimed not only to understand the history of photojournalism but also to explore the photographic styles and types employed by the newspaper O Progresso over the studied decades. Annual editions of the newspaper spanning 53 years were analyzed, totaling 334 examined photographs. This approach allowed for identifying the maturation of photojournalism and the criteria used, with a focus on visual coverage objectivity. The methodology involved carefully selecting one edition per year, specifically choosing the edition released in May, which was essential to ensure a balanced representation across the years and capture any seasonal or thematic changes during each period. Additionally, the study analyzed the newspaper covers to understand how images were used as immediate visual narratives, influencing readers’ perception of key events and topics. During the investigation of sports and politics sections, the choices of images and their contribution to journalistic storytelling were observed. The application of photographic styles facilitated an analysis of the different approaches and intentions behind the selected images.The comparison of images over time revealed trends, changes, and continuities in the photojournalistic coverage of the newspaper O Progresso. These results provided a broader understanding of visual representation patterns, the evolution of photographic techniques, and shifts in editorial priorities throughout the studied decades. These findings were visually presented in a chronological graph. Notably, the production of photojournalistic content has been consistent since the newspaper’s inception, with a significant increase in the use of cover photos. This shift reflects a change in editorial priorities toward a more visually oriented journalistic communication. Thus, the growing importance of images in modern journalistic narratives is evident.